PENGARUH PELATIHAN PEMASARAN DIGITAL DAN PERAN MEDIA SOSIAL TERHADAP PENGEMBANGAN UMKM SIDOARJO - Purnawan, Steven Owen (Universitas Serang Raya, 2024)
MSMEs have an important role in the local economy, including in Sidoarjo Regency. However, MSMEs often face various marketing problems and challenges. The research aims to examine the influence of digital marketing training and the role of social media on the development of MSMEs in Sidoarjo Regency, with the help of the SmartPLS version 4 application using the SEM-PLS method. This research involved 100 permanent respondents who had taken part in digital marketing training organized by the Sidoarjo Regency Cooperatives and Micro Enterprises Service. Data was collected via a Google Form questionnaire and analyzed using SmartPLS version 4. The research showed that digital marketing training had a positive influence on the role of social media, and then digital marketing training and the role of social media had a positive influence on the development of MSMEs in Sidoarjo Regency. This research indicates that the use of digital marketing training and social media can be an effective strategy in increasing the competitiveness and growth of MSMEs in current technological developments.